THE PRONUNCIATION COMPONENT IN ESL LESSONS: TEACHERS’ BELIEFS AND PRACTICES - Shah, Shanina Sharatol Ahmad; Othman, Juliana; Senom, Fatiha (Universitas Pendidikan Indonesia, 2017)
Research has shown that teachers’ beliefs on teaching and learning exert an influence on their actual classroom practices. In the teaching of English pronunciation, teachers’ beliefs play a crucial role in the choice of pronunciation components taught in the ESL classrooms. This paper explores teachers’ beliefs about teaching English pronunciation in Malaysian classrooms and the extent to which these beliefs influenced the teachers’ classroom instructions. Employing a multiple case study of five ESL teachers in secondary schools, this study investigated the beliefs the teachers have formed about pronunciation focused areas and classroom practices in teaching English pronunciation. Data were collected through actual classroom observations and semi-structured interviews with the teachers and students. The findings of the study found that ESL teachers seem to believe that pronunciation skills are to be taught integratedly with other English language skills. Results also indicate a discrepancy between these teachers’ beliefs on the focused areas of pronunciation and the stated curriculum specifications. Additionally, the ESL teachers seem to have vague and contradictory beliefs about pronunciation focused areas. These beliefs are based on their previous language learning and professional experience as well as other contextual factors such as examination demands and time constraints. As a result, these beliefs lead to the pronunciation component being neglected despite it being stipulated by the curriculum.